A case for geography in South African senior primary schools: an analysis and evaluation of current geographical thinking and practice - Taylor, Simon Michael (Rhodes University, Faculty of Education, Department of Education, 1995)
Geography faces several challenges in a changing South Africa. These include the challenge to initiate a primary curriculum that helps to provide a foundation for sustainable living in a society that faces serious problems of unemployment, violence, irreparable damage to the environment and the lack of housing, water and basic services for the majority of the population. This thesis attempts to provide a case for geography in the primary school by examining the value of the subject for pupils' development and by reviewing the strengths and weaknesses of an integrated approach in view of the possible introduction of an integrated primary curriculum in South Africa. The second aspect of the study is concerned with a survey of teachers in the Natal Education Department to evaluate the perceived value of geography as a subject and support for geography as a discrete subject. The main thrust of geography in the primary school is to develop concepts, skills, values and attitudes that allow pupils to be more understanding and caring about the local and global environment, about people, communities, species and the natural environment on which we all depend. The results of the survey reveal that teachers support geography as a discrete subject with an intra-curriculum approach. The introduction of an integrated core curriculum in South Africa would prove problematic as teachers are not in favour of an integrated approach across the curriculum. The lack of teacher support in Kenya for an integrated curriculum was one of the main reasons for its failure. Hopefully South Africa will learn from other countries experiences with introducing an integrated curriculum. Teachers value the role of geography in the education of the child and suggest the introduction of environmental and development themes to make the subject more relevant to children's lives. The syllabus analysis revealed that a unified pnmary curriculum is required which is influenced by the needs of society in South Africa. Recommendations are made regarding ideas for a future primary curriculum.
Keywords: Geography -- Study and teaching (Elementary) -- South Africa -- Evaluation; Geography teachers -- South Africa -- Attitudes; Geography -- Study and teaching (Elementary) -- Curricula -- Comparative studies